Universal or targeted approaches? an experiment about heat risk messaging - Yajie Li; Peter D. Howe (Natural Hazards, 2023)

Geographic and demographic variation in worry about extreme heat and COVID-19 risk in summer 2020 - Peter D. Howe; Olga V. Wilhelmi; Mary H. Hayden; Cassandra O'Lenick (Applied Geography, 2023)

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Perceptions of seasonal weather are linked to beliefs about global climate change: evidence from Norway - Peter D. Howe (Climatic Change, 2018)

Correction to: The spatial distribution of Republican and Democratic climate opinions at state and local scales - Matto Mildenberger; Jennifer R. Marlon; Peter D. Howe; Anthony Leiserowitz (Climatic Change, 2018)

The spatial distribution of Republican and Democratic climate opinions at state and local scales - Matto Mildenberger; Jennifer R. Marlon; Peter D. Howe; Anthony Leiserowitz (Climatic Change, 2017)

Stress and neuroinflammation: a systematic review of the effects of stress on microglia and the implications for mental illness - Marilia A. Calcia; David R. Bonsall; Peter S. Bloomfield; Sudhakar Selvaraj; Tatiana Barichello; Oliver D. Howes (Psychopharmacology, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

Mapping the shadow of experience of extreme weather events - Peter D. Howe; Hilary Boudet; Anthony Leiserowitz; Edward W. Maibach (Climatic Change, 2014)

Public perceptions of rainfall change in India - Peter D. Howe; Jagadish Thaker; Anthony Leiserowitz (Climatic Change, 2014)

Knee extensor strength differences in obese and healthy-weight 10-to 13-year-olds - Margarita D. Tsiros; Alison M. Coates; Peter R. C. Howe; Paul N. Grimshaw; Jeff Walkley; Anthony Shield; Richard Mallows; Andrew P. Hills; Masaharu Kagawa; Sarah Shultz; Jonathan D. Buckley (European Journal of Applied Physiology, 2013)

A support system for assessing local vulnerability to weather and climate - Alex Coletti; Peter D. Howe; Brent Yarnal; Nathan J. Wood (Natural Hazards, 2013)

Mass-Spring Model for Simulation of Heart Valve Tissue Mechanical Behavior - Peter E. Hammer; Michael S. Sacks; Pedro J. del Nido; Robert D. Howe (Annals of Biomedical Engineering, 2011)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)